A musealidade no Museu Gruppelli, Pelotas/RS: entre o visível e o invisível. - Brahm, José Paulo Siefert (2017)
The main objective of this research is to analyze the museum's perception of the objects exhibited at the Gruppelli Museum in the rural area of Pelotas, RS, as well as its potential to evoke memories and forge identities. Anchored in this objective, we will seek to clarify the following questions: does the public that visit the Gruppelli Museum and its exhibitions recognize it as a propitious space for evocation of memories and identity affirmation? What memories do the evoked objects evoke: individual, shared or both? What are the connections that people make when they observe the exhibits? As a methodological procedure, we used, above all, the interview (face-to-face) and also the researcher's observation. It should be mentioned that the interviews were applied to the visitors of the Museum, whether they live in rural or urban areas during the visitation. In this way, we realize that the memorial work is facilitated by the physicality of the objects that guide our analysis, the scythe and the cart, and by the connection of these with other exposed objects. The research presented here becomes relevant because it is at the heart of the contemporary discussions that touch on social memory and cultural heritage, for shedding light on how people appropriate, signify and use patrimony, in order to affirm (or answer) Their memories and identities. In the same way, it is also of interest to the field of museums, because it seeks to understand how the public that visits the Gruppelli Museum perceives and relates to patrimonial assets taken care of in the exhibition space, having as reference the concept of museality - concept that is recognized As one of the main objects of study of Museology. This time, we tried, with this study, to solidify and create new disciplinary bridges between the areas (memory, heritage and museum). At the same time, it attempts to interrelate and observe the approaches and conceptual boundaries of both to the areas.